The Social Network of Creative Economy Actors in the Padang City Tourism Destination Area, West Sumatra - Zusmelia; Ansofino; Irwan; Jimi Ronald (Universitas Pendidikan Ganesha, 2023)
In order to maintain the integrity of the welfare of the Indonesian people after the COVID-19 pandemic, the creative economy in Indonesia will continue to survive and develop as the foundation of people's lives. For this reason, this research was conducted. The focus of the study in this study was to analyze the typology of the social network of creative economic actors in the Tourism Destination Area of Padang City. This research combines two approaches, namely qualitative and quantitative approaches, which is called a mixed methods approach. Data collection techniques were carried out in several ways, namely by observation, in-depth interviews, document studies and survey techniques or structured interviews. This research focuses on the creative economy sub-sectors in the fields of crafts, music and culinary. The unit of analysis is at the individual and group levels of creative economy actors in the tourist destination area of Padang City, West Sumatra. The results showed that the highest creative economy sub-sector in the tourist destination of Padang City was crafts by 33 percent, music and culinary 23 percent. Creative economy actors strengthen social networks through kinship, friendship and digital or social media. In general, these strengths strengthen ties in marketing and ties only at the micro level. The conclusion of this study is that the social networks carried out by EKRAF actors are still in primordial bonds.